2016
DOI: 10.1016/j.postharvbio.2015.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Sanitisation of fresh-cut celery and radicchio by gas plasma treatments in water medium

Abstract: The antimicrobial efficacy of dielectric barrier discharge atmospheric gas plasma (DBD) was tested against Listeria monocytogenes and shigatoxin-producing Escherichia coli serogroups O157 and O26. Challenge tests were carried out with samples of cut celery and radicchio leaves inoculated with a mix of five strains of L. monocytogenes or the two strains of E. coli immersed in deionised water. The treatment efficacy was also assessed considering only the contaminated deionised water.For deionised inoculated wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…In the case of PAW treatment of fresh food, Ma et al (2016) observed acceleration in fruit ripening due to the oxidative species in PAW for Chinese bayberries causing a faster fruit decay with higher treatment times. They claimed that the prevention of fruit decay by PAW was not a dose-dependent effect, in contrary to the findings by others (Berardinelli et al, 2016;Herceg et al, 2016;Scholtz et al, 2010;Tang et al, 2008). Therefore, NTP and PAW treatment conditions and the resulting bactericidal properties in nonfood substrates could be completely different from food materials.…”
Section: Ntp-liquid Interactions In Foodmentioning
confidence: 83%
See 3 more Smart Citations
“…In the case of PAW treatment of fresh food, Ma et al (2016) observed acceleration in fruit ripening due to the oxidative species in PAW for Chinese bayberries causing a faster fruit decay with higher treatment times. They claimed that the prevention of fruit decay by PAW was not a dose-dependent effect, in contrary to the findings by others (Berardinelli et al, 2016;Herceg et al, 2016;Scholtz et al, 2010;Tang et al, 2008). Therefore, NTP and PAW treatment conditions and the resulting bactericidal properties in nonfood substrates could be completely different from food materials.…”
Section: Ntp-liquid Interactions In Foodmentioning
confidence: 83%
“…Berardinelli et al. () also stated that the inactivation efficiency of PAW varies with respect to the kind of vegetables. Almeida et al.…”
Section: Ntp–liquid Interactions In Foodmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the maximum temperature of apple surface treated with plasma reached 51°C, it was below the threshold for thermal killing of the pathogens. Similarly, DBD atmospheric plasma applied in the study of Berardinelli et al (2016) appeared to be a potential sanitising technology for decontamination of L. monocytogenes and E. coli O157 and O26 producing shiga toxin. On spinach, oxygen NTP gave the higher efficacy than washing method using 3% concentration of hydrogen peroxide.…”
Section: Elimination Of Microbes By Ntpmentioning
confidence: 99%